A prospective study of influenza infections during pregnancy. Issue 2 (June 1980) - Griffiths, P D; Ronalds, C J; Heath, R B
Abstract : Serological evidence of infection with influenza A and B viruses was sought during three successive winters. Paired sera from 1595 pregnant women were studied and 79 infections occurred in 77 women (4.8%). A further 77 women who had no serological evidence of recent influenza infection were selected from the study population to serve as a control group. Cases and controls were comparable with respect to age, race, marital status, and number of previous pregnancies. Their offspring had virtually identical mean birth weights, skull circumferences, lengths, and incidences of neonatal jaundice. Although all the infections occurred in either the second or the third trimesters of pregnancy, the cases delivered more babies with congenital abnormalities than did the controls. The possibility was considered that the presence of an abnormal fetus made these women more susceptible to influenza infection. Unexpectedly, the women experiencing influenza infection during pregnancy delivered an excess of male babies, and an excess of females was born to the controls. Although this difference was statistically highly significant (P < 0.01), a biological explanation for the results was not readily apparent and it is suggested that future studies of influenza during pregnancy should particularly look for evidence of an altered sex ratio.